Health and subjective well-being in later adulthood: Different health states - different needs? - Schüz, Benjamin; Wurm, Susanne; Warner, Lisa Marie; Tesch-Römer, Clemens (Applied Psychology: Health and Well-Being, 2009)
From midlife on, health problems become more prevalent. Health is one of the key determinants of subjective well-being (SWB), but examining the relation between health and SWB in later adulthood is complicated by the clustering of multiple illnesses. This article proposes Latent Class Analysis (LCA) for a parsimonious description of adult health. This article compares SWB in health classes and examines the relative importance of socioeconomic resources, pain and coping (flexible goal adjustment) for SWB. Data stem from a nation-wide representative sample of adults aged 40201385 (German Ageing Survey, DEAS; N = 3,084). LCA was used to examine different configurations of health. Multiple regression analyses in latent classes were conducted to examine predictors of SWB. LCA generated four distinct classes of health conditions: No disease (n = 807), cardiovascular diseases (n = 405), joint problems (n = 1,612) and multiple illnesses (n = 258). As expected, only small mean differences in SWB indicators were found, whereas discontinuous predictors of SWB were detected: Coping was more strongly associated with SWB in individuals with higher illness burden. LCA can be applied to describe health in later adulthood. Differential prediction patterns suggest distinct factors for SWB depending on individual health status.
Keywords: adult health; developmental psychology; Germany; health psychology; health status; latent class analysis; later adulthood; resource appraisal; subjective well-being